Role of mitochondrial quality surveillance in myocardial infarction: From bench to bedside - Zhou, Hao; Ren, Jun; Toan, Sam; Mui, David (Ageing research reviews, 2021)
•Mitochondrial quality surveillance is regulated by a variety of adaptive responses.•Mitochondrial fission favors the elimination of depolarized mitochondria through mitophagy.•The double-edge sword of mitophagy needs to be taken into consideration in the conception of new pharmacological approaches to treat MI.•Mitochondrial biogenesis represents a regenerative program to replace old and damaged mitochondria with new and healthy ones.•Mitochondrial bioenergetics is regulated by a metabolic switch between glucose and fatty acid usage, depending on oxygen availability. Myocardial infarction (MI) is the irreversible death of cardiomyocyte secondary to prolonged lack of oxygen or fresh blood supply. Historically considered as merely cardiomyocyte powerhouse that manufactures ATP and other metabolites, mitochondrion is recently being identified as a signal regulator that is implicated in the crosstalk and signal integration of cardiomyocyte contraction, metabolism, inflammation, and death. Mitochondria quality surveillance is an integrated network system modifying mitochondrial structure and function through the coordination of various processes including mitochondrial fission, fusion, biogenesis, bioenergetics, proteostasis, and degradation via mitophagy. Mitochondrial fission favors the elimination of depolarized mitochondria through mitophagy, whereas mitochondrial fusion preserves the mitochondrial network upon stress through integration of two or more small mitochondria into an interconnected phenotype. Mitochondrial biogenesis represents a regenerative program to replace old and damaged mitochondria with new and healthy ones. Mitochondrial bioenergetics is regulated by a metabolic switch between glucose and fatty acid usage, depending on oxygen availability. To maintain the diversity and function of mitochondrial proteins, a specialized protein quality control machinery regulates protein dynamics and function through the activity of chaperones and proteases, and induction of the mitochondrial unfolded protein response. In this review, we provide an overview of the molecular mechanisms governing mitochondrial quality surveillance and highlight the most recent preclinical and clinical therapeutic approaches to restore mitochondrial fitness during both MI and post-MI heart failure.